x = 3
Step-by-step explanation:
First we would simplify the left hand side of the equation by expanding the brackets
so 2(4-3x) = 8-6x and
5(2x-3) = 10x-15
This gives the left hand side as 8-6x+10x-15. So the overall equation becomes
8-6x+10x-15 = 20-5x.
Grouping the unknown values on one side and integers on one side of the equation gives us
8-15-20=6x-10x-5x (note the sign changes when numbers and unknown values are moved to the other side of the = sign
Solving further, -27 = -9x i.e x = -27/-9 = 3
Hence x = 3
Answer:
3
The value of when the value of is multiplied by is .
According to the statement, we have the following relationship:
(1)
Where:
- Independent variable.
- Dependent variable.
- Proportionality constant.
We can eliminate the proportionality constant by constructing the following relationship:
If we know that , , and , then the value of when the value of is multiplied by is:
DON'T SEARCH FOR ANYTHING ON THE WEB OR THE INTERNET IS A SINGLE PAGE
x/2 + 10 = 35 - 2x
x/2 + 2x = 35 - 10
5x/2 = 25
5x = 25.2
5x = 50
x = 50/5
x = 10
The number is 10
2.64 is greater than 1.9
answer is (d) 4/3
-x+3/7=2x-25/7
25/7+3/7=2x+x
28/7=3x
4=3x
x=4/3